Metabolism of alcaligenes denitrificans in biofilm vs planktonic cells - Teixeira, P. (2002)
Aims: To compare the effect of phosphorous concentration (200 mg P 1-1 and 20 mg P 1-1) on the denitrifying efficiency of Alcaligenes denitrificans when in the form of planktonic cells or in the form of a biofilm, and to select the most adequate C/N ratio. Methods and Results: Two types of assays were carried out: with planktonic cells and with cells in biofilm form. Anoxic bottles with the appropriate C/N and phosphorous concentration were incubated at 30°C and submitted to orbital shaking at 150 rev min-1. The specific activity of cells in biofilm form, in terms of substrate consumption, was significantly higher than cells in planktonic form. With regard to the effect of increasing phosphorous concentration, an increase in specific activity was also only evident when the cells were in biofilm form. Conclusions: The two forms showed different performances and phosphorous concentration only markedly affected the biofilm form. Significance and Impact of the Study: The importance of the C/N/P ratio in the denitrification process is demonstrated. As there was no report in the literature about the stoichiometric relationship of heterotrophic denitrification with citrate, its stoichiometry, including the requirement for cell synthesis, was determined.